Methods of delivering oral hygiene instructions among orthodontic patients: the past, current and future - Deborah Anne Nathan; Dhanaraju Noor Sam Ahmad; Nurul Asyikin Yahya; Asma Alhusna Abang Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
This review paper aims to present the evolution in methods of delivering oral hygiene information to orthodontic patients. Orthodontic fixed appliance treatment confers numerous benefits to patients in terms of occlusion, function and aesthetics, but it is associated with unwanted consequences due to challenges in maintaining oral hygiene. The ways of delivering oral hygiene information to patients have progressed over the years. Recent years have seen an increase in the popularity of incorporating technology in delivering oral hygiene information and monitoring of oral hygiene practices. The use of video-based instructions to web-based platforms such as Massive Open Online Course (MOOC) and social media platforms such as YouTube, Instagram and TikTok have all become a mode of oral hygiene information conveyance. Mobile apps are now a popular means to keep track of oral care practices such as toothbrushing frequency. The active ingredients of oral care products have improved providing a greater anticariogenic and antiplaque effect to the user as have the design of toothbrushes and even dental floss. In the future, more advanced technology may be used, such as artificial intelligence (AI) and machine learning, to create intelligent machines that can help educate patients on oral health maintenance and improvement.